Answer:
For some reason user my answer to this question was deleted for being incorrect, but it WAS in fact CORRECT.
To repeat:
g(f(-2)) is equal to 12
Step-by-step explanation:
We can solve this simply by first applying function f() to -2, and applying function g() to the value returned:
f(x) = x² + 6
f(-2) = -2² + 6
= 4 + 6
= 10
g(x) = 2x - 8
g(10) = 2 × 10 - 8
= 20 - 8
= 12
Further to that, you can also solve this by applying function g to the function f itself, giving you a single function to find the value:
g(f(x))
= 2f(x) - 8
= 2(x² + 6) - 8
= 2x² + 12 - 8
= 2x² + 4
We can now plug the original -2 value in there to confirm our result
2(-2)² + 4
= 2 × 4 + 4
= 8 + 4
= 12